Program Psikoedukasi Penjurusan Untuk Meningkatkan Kemampuan Pengambilan Keputusan Dalam Memilih Sekolah Lanjutan Atas - Erniwati, Erniwati; , Dr. Lisnawati Ruhaena, M.Si.Psikolog; , Dra. Zahrotul Uyun, M.Si.Psikolog (2017)
This research aims to empirically study the influence of majors psychoeducation program on the ability of making decision in selecting a senior high school. Subjects of the research are as many as 34 students who are the students of junior high school in SMP Muhammadiyah 5 Surakarta. The subjects were divided into two groups,which is experimental and control groups, each groups consisting of 17 participants. The experimental group was given treatment in the form of psychoeducation while the control group was not given treatment. The method used in this research is the experimental pretest-posttest cotrol group design. The determination of the subject of the control group and the experimental group was conducted by using the random assignment. The materials conveyed in the psychoeducation are self-analysis, insight enrichment, skill domain, self-confidence, and goal determination by using the method of SMART. The ability of decision-making's data were measured by ability of decision-making scale with CVR's score between 0.2 to1 and the reliability's score was 0.817.The result of the hypothesis test in this research using the Independent Sample Sample T Test whit Sig 0,000 (p<0,01), that means that there is a significant differencce in the increase of the ability of making decision between the group which was given with psychoeducation and the group which was not given any psychoeducation. Therefore, psychoeducation is effective in increasing the ability of making decision.